Limits of the possible: diagnostic image quality in coronary angiography with third-generation dual-source CT - Ochs, Marco; Siepen, Fabian aus dem; Fritz, Thomas; André, Florian; Korosoglou, Grigorios; Seitz, Sebastian; Schlett, Christopher L.; Kauczor, Hans-Ulrich; Friedrich, Matthias; Katus, Hugo; Buß, Sebastian Johannes (Clinical research in cardiology, 2017)
The usage of coronary CT angiography (CTA) is appropriate in patients with acute or chronic chest pain; however the diagnostic accuracy may be challenged with increased Agatston score (AS), increased heart rate, arrhythmia and severe obesity. Thus, we aim to determine the potential of the recently introduced third-generation dual-source CT (DSCT) for CTA in a 'real-life' clinical setting.